Perspectives on Next Steps in Classification of Orofacial Pain – Part 1: Role of Ontology - Ceusters, Werner (J Oral Rehabil, 2015)
The purpose of this paper is to review existing principles of orofacial pain classifications and to specify design recommendations for a new system that would reflect recent insights in biomedical classification systems, terminologies and ontologies. The paper was initiated by a symposium organized by the International RDC/TMD Consortium Network in March 2013, to which the present authors contributed. The following areas are addressed: problems with current classification approaches, status of the ontological basis of pain disorders, insufficient diagnostic aids and biomarkers for pain disorders, exploratory nature of current pain terminology and classification systems, and problems with prevailing classification methods from an ontological perspective. Four recommendations for addressing these problems are: 1) develop a hypothesis-driven classification structure built on principles that ensure to our best understanding an accurate description of the relations among all entities involved in orofacial pain disorders; 2) take into account the physiology and phenomenology of orofacial pain disorders in order to adequately represent both domains including psychosocial entities in a classification system; 3) plan at the beginning for field-testing at strategic development stages; and 4) consider how the classification system will be implemented. Implications in relation to the specific domains of psychosocial factors and biomarkers for inclusion into an orofacial pain classification system are described in two separate papers.